Variability study of the high-mass X-ray binary IGR J18027−2016 with Swift-XRT. Issue 2 (16th August 2016) - Aftab, Nafisa; Islam, Nazma; Paul, Biswajit
Abstract: We report the results from pulsations and spectral analysis of a large number of observations of the high-mass X-ray binary pulsar IGR J18027−2016 with Swift X-ray Telescope (XRT), carried out at different orbital phases. In some orbital phases, as seen in different XRT observations, the X-ray intensity is found to vary by a large factor, of about ∼50. In all the observations with sufficient number of source X-ray photons, pulsations have been detected around the previously known pulse period of ∼140 s. When detected, the pulse profiles do not show any significant variation over a flux difference of a factor of ∼3. The absorption column density is found to be large before and after the eclipse. We discuss various possible reasons for intensity and spectral variations in IGR J18027−2016, such as clumpy wind and hydrodynamic instabilities.